The localization of the larvae of the nostril fly (Cephenemyia trompe L) in the pharynx of reindeer in an earlier unknown tonsil tissue - Rehbinder, Claes; Nordkvist, Magnus (Rangifer, 1983)
The localization of the larvae of the reindeer nostril fly (Cephenemyia trompe L) in the pharynx was investigated in 21 reindeer, 11 months old, during April, and in 5 animals during November. In reindeer, without the presence of larvae, no preformed pharyngeal pouch was found at the predilection site, dorsomedially in the pharynx, but an unpaired tronsil, tentatively named Tonsilla pharyngis dorso-medialis. In 12 of the animals investigated during April, a puch containing larvae of C. trompe was found at the predilection site, i.e. the site of the dorsomedially located tonsil. Histologically remnants of tonsil tissue was present at the opening of the pouch. In 3 animals a pouch, containing larvae, was found in the left lateral wall and in 2 animals in the right lateral wall of the pharynz between the opening of Tuba auditiva and the tonsil. In one animal 2 pouches were found, one in the tonsil tissue and one located in the right lateral wall of pharynx. In serial sections from two animals investigated during November, 1 :st instar larvae of Cephenomyia trompe were found in the crypts of the tonsills. The fact that the tonsil tissue is a predilection site for C. trompe larvae may be due to the mechanical protection the 1st instar larvae can find in the crypts. Larvae may, however, also attach to other parts of the pharyngeal mucosa. During their development the larvae penetrate the mucosa forming a pouch. The wall of this pouch consists of a naked acute granulation tissue heavily infiltrated with eosinophilic leucocytes. In connection with the healing process, starting when the larvae have left, a pouch may remain, characterized by walls of chronic granulation tissue covered by a mucous membrane. This pouch could well be misinterpreted as a preformed pouch. Lokalisationen av svalgkormflugans (Cephenemyia trompe L) larver i svalget på ren i en tidigare okänd tonsillvävnad (Tonsilla pharyngis dorso-medialis). Abstract in Swedish / Sammanfattning: Lokalisationen av svalgkormflugans (Cephenemyia trompe L) larver i svalget på ren undersøktes. Resultaten av undersokningen visade att någon preformerad svalgficka inte forekommer hos ren, utan att på den plats dår fickor innehållande larver vanligtvis påvisas år belågen en oparig tonsillvåvnad, forslagsvis kallad Tonsillapbaryngis dorsomedialis. Hos djur infekterade med svalgkormlarver forelåg i april de fiesta fickbildningarna i anslutning till tonsillvåvnaden men fickor forekom också hoger- och vånstersidigt i svalgslemhinnan. I ett fall påvisades två fickor, en i tonsillvåvnaden och en hogersidigt i svalgslemhinnan. Fickornas vågg utgjordes vid denna årstid av en akut ej slemhinneforsedd granulationsvåvnad rikligt infiltrerad med eosinofila leukocyter. Hos novemberrenarna påvisades lsta stadiets larver av C. trompe i tonsillens kryptor. Hos en åldre ren forelåg omedelbart vid sidan av tonsillen en fickbildning, vars vågg besto av kronisk granulationsvåvnad beklådd med slemhinna. Tonsillvåvnadens roll som predilektionsplats for larvernas utveckling diskuteras.